An empirical study, role and importance of visual merchandising in retail branding- A practitioners’ perspective - Rebeiro, Damian (2015)
The aim of this research is to analyze the role and importance of Visual merchandising and below the line advertising on retail branding. An initial investigation on “visual merchandising” is undertaken along with its effects on consumer’s purchase behavior and brand identity. The research is based on the companies in Dubai, which represents the Middle East and African market. Semi - Structured Interviews of various practitioner based in Dubai were undertaken in order to understand the topic deeper. A brief study of Visual Merchandising in integrated marketing communication, Brand Identification through visual merchandising, Visual Merchandising Communication Process, Visual Merchandising against competition, BTL advertising, ATL advertising and TTL advertising, its relationship with various advertising theories and Procurement of Visual merchandising materials was undertaken to establish this research. The focus of the study is mainly on the consumer electronics, brands, distributors and retailers such as Toshiba, Pioneer, Samsung, LG, Carrefour, Emax, Eros, Hitachi, Samsung, Al Futtaim- Toshiba, JVC KENWOOD, P&G, RB and TCL were used in this study. An ethnography study of various retail outlets were undertaken to provide examples in this paper. Exploratory research was also undertaken by analyzing past research papers of visual merchandising. This paper just throws a light on BTL advertising as visual merchandising is concluded as a part of the same; In-depth study of visual merchandising was mainly focused.